Pemberdayaan Karyawan Dalam Penerapan Keselamatan dan Kesehatan Kerja Berbasis Fault Tree Analysis - Muhammad Yusuf; Titin Isna Oesman; Nugroho Adi Wicaksono (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
WL Aluminium industry is a small and medium enterprises which is engaged in the production of household needs and there is no unit that manages the Occupational Health and Safety (OHS). Meanwhile the employee were not encouraged in OHS implementation. This study aims to determine the management system of occupational health and safety management, the dangers of work accidents and the factors causing occupational accidents that occur in the WL Aluminium company. The methods used are Fault Tree Analysis (FTA) approaches that encourage the employee based on Hazard Identification Risk Assessment (HIRA) and SWOT analysis. The results of the research can be seen in the HIRA method there are 3 (three) production activities that have a high enough risk rating number (RRN). The main cause of work accidents with the FTA method is the potential for workplace accidents that occur, namely the fingers are exposed to aluminium raw materials, the hands are exposed to hot printing containers, pain in the arms, fingers are affected by lathe eyes and back pain. For the SWOT matrix strategy, the methods used by the company to achieve good growth include employee participation through creating an OHS team for monitoring and evaluating the implementation of the OHS program, creating an administrative system aimed at managing the OHS management system, as well as socializing about OHS, empowerment of the employee in OHS implementation and the goal of zero accident can be achieved.